Financial Affordability, Health Insurance, and Use of Health Care Services by the Elderly: Findings From the China Health and Retirement Longitudinal Study. (September 2019) - Ren, Jiaojiao; Ding, Ding; Wu, Qunhong; Liu, Chaojie; Hao, Yanhua; Cui, Yu; Sun, Hong; Ning, Ning; Li, Ye; Kang, Zheng; Shan, Linghan; Zhao, Miaomiao; et al.
The rapidly growing aging population has attracted global attention. This study explores the associations between 3 basic health insurances, and it identifies factors associated with health care services among the elderly populations. This study is based on multistage stratified cluster sampling method from the 2013 China Health and Retirement Longitudinal Study (CHARLS) resulting in 7589 participants. Medical Insurance for Urban Employees (MIUE) members were more likely to use inpatient health care services. Health insurance programs were associated with inpatient services usage but not outpatient services usage. There are significant disparities in medical costs and health care service usage among the 3 insurance programs. Health insurance program is only associated with inpatient care. These findings may provide some suggestions to support improvements to the Chinese health care system.